IMPROVING STUDENTS’ READING COMPREHENSION OF GRADE VIII AT SMP N 3 TOLITOLI UTARA THROUGH THINK ALOUD STRATEGY - Darwin Darwin (Jurnal Madako Education, 2019)
The objective of this study is to prove that think aloud can improve students’ reading comprehension. The sample of this research is class VIII B of SMP N 3 Tolitoli Utara in 2016/2017 academic year that selected by using purposive sampling technique. The total number of sample is 20 students.  Instrument which is used to collect data is test. The data is analyzed by using statistical analysis in order to know the significant difference of the achievement of the students’ in pre-test and post-test..The mean scores of the students’ score in the pre-test is37.60 and mean score in the post-test is68.70. Based on the result of the statistical computation, the result of data analysis shows that there is a significant difference between the result of pre-test and post-test. By applying 0,05 level Of significant the researcher find out that tcounted11.945 is higher than ttable2.093. It implies that there is a significant improvement on students’ reading comprehension. In short, the application of think aloud can improvereading comprehension of the eight grade students of SMP N 3 Tolitoli Utara.  Key words: Improving, Reading Comprehension, Think Aloud.